IMPACT OF COVID-19 VACCINE ON PEOPLE: A CASE STUDY - Aggarwal, Amrita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research explores the multifaceted impact of COVID-19 vaccines on physical, mental, and social well-being among residents of Mumbai, India. It examines the effectiveness of vaccines in mitigating severe illness and hospitalizations while highlighting the physical side effects and their management. Mental health dynamics are analyzed, emphasizing reduced anxiety and improved perceptions of safety post-vaccination, though some individuals reported persistent stress and concerns. Socially, the study reveals enhanced participation in group activities and improved community resilience, yet notes challenges in addressing misinformation and vaccine hesitancy. A mixed-method approach was employed, combining secondary data and primary survey responses from individuals aged 18-50. The survey captured experiences with physical side effects, emotional changes, and perceptions of vaccine rollout efficiency. Key findings include a high vaccination rate (97.3%) among respondents, with Covishield being the most administered vaccine. Despite minor side effects, most respondents managed them effectively through rest and hydration. Social dynamics shifted positively, with increased confidence in engaging in public and social activities. The study also underscores disparities in vaccine access and the need for targeted communication strategies to counter misinformation. Recommendations emphasize prioritizing mental health through transparent communication, equitable vaccine distribution, and addressing logistical barriers. The study concludes by advocating for a collaborative approach involving governments, healthcare providers, and communities to enhance vaccine acceptance and efficacy, thereby mitigating the pandemic’s multifaceted impact.